Association between polycyclic aromatic hydrocarbon exposure and peripheral blood mononuclear cell DNA damage in human volunteers during fire extinction exercises. (13th October 2017) - Andersen, Maria Helena Guerra; Saber, Anne Thoustrup; Clausen, Per Axel; Pedersen, Julie Elbæk; Løhr, Mille; Kermanizadeh, Ali; Loft, Steffen; Ebbehøj, Niels; Hansen, Åse Marie; Pedersen, Peter Bøgh; Koponen, Ismo Kalevi; Nørskov, Eva-Carina; et al.
Abstract: This study investigated a number of biomarkers, associated with systemic inflammation as well as genotoxicity, in 53 young and healthy subjects participating in a course to become firefighters, while wearing personal protective equipment (PPE). The exposure period consisted of a 3-day training course where the subjects participated in various live-fire training exercises. The subjects were instructed to extinguish fires of either wood or wood with electrical cords and mattresses. The personal exposure was measured as dermal polycyclic aromatic hydrocarbon (PAH) concentrations and urinary excretion of 1-hydroxypyrene (1-OHP). The subjects were primarily exposed to particulate matter (PM) in by-stander positions, since the self-contained breathing apparatus effectively prevented pulmonary exposure. There was increased dermal exposure to pyrene (68.1%, 95% CI: 52.5%, 83.8%) and sum of 16 polycyclic aromatic hydrocarbons (ƩPAH; 79.5%, 95% CI: 52.5%, 106.6%), and increased urinary excretion of 1-OHP (70.4%, 95% CI: 52.5%; 106.6%) after the firefighting exercise compared with the mean of two control measurements performed 2 weeks before and 2 weeks after the firefighting course, respectively. The level of Fpg-sensitive sites in peripheral blood mononuclear cells (PBMCs) was increased by 8.0% (95% CI: 0.02%, 15.9%) compared with control measurements. The level of DNA strand breaks was positively associated with dermal exposure to pyrene and ƩPAHs, and urinary excretion of 1-OHP. Fpg-sensitive sites were only associated positively with PAHs. Biomarkers of inflammation and lung function showed no consistent response. In summary, the study demonstrated that PAH exposure during firefighting activity was associated with genotoxicity in PBMCs.